Selecting Research Areas and Research Design Approaches in Distance Education: Process Issues - Passi, B. K.; Mishra, Sudarshan (International Review of Research in Open and Distributed Learning, 2004)
The purpose of this paper is to study the process used for selecting research areas and methodological approaches in distance education in India. Experts from the field of distance education in India were interviewed at length, with the aim of collecting qualitative data on opinions on process-issues for selecting areas for research, research design, and appropriate methodological approaches in distance education. Data collected from these interviews were subjected to content analysis; triangulation and peer consultation techniques were used for cross-checking and data verification. While the findings and recommendations of this study have limited application in that they can only be used in the specific context outlined in this paper, respondents in this study nonetheless revealed the pressing need for more process-oriented research in examining media and technology, learners and learning, and distance learning evaluation processes. Our research, which yielded interesting empirical findings, also determined that a mixed approach – one that involves both quantitative and qualitative methods – is more appropriate for conducting research in distance education in India. Qualitative evidence from our research also indicates that respondents interviewed felt that emphasis should be placed on interdisciplinary and systemic research, over that of traditional disciplinary research. Research methods such as student self-reporting, extensive and highly targeted interviews, conversation and discourse analysis, were determined to as useful for data collection for this study.